"Triple Leidenfrost" effect spotted in two bouncing droplets. (1st February 2022) - Jarman, Sam
Abstract : A new type of Leidenfrost effect that causes droplets of different liquids to bounce off each other when placed on a hot surface has been discovered by researchers in Mexico and France.